Moderasi Kecerdasan Buatan dalam Hubungan Perkembangan Mahasiswa dengan Peningkatan Prestasi dan Kepuasan Belajar di STIE Cendekia Karya Utama Semarang - Yudho Purnomo (OPTIMAL Jurnal Ekonomi dan Manajemen, 2024)
This study aims to analyze the role of artificial intelligence (AI) implementation as a moderating variable in the relationship between student development and the implications of AI use on improving academic outcomes and student learning satisfaction. The focus of the study was directed at students of the Economics Study Program at STIE Cendekia Karya Utama Semarang with a total of 38 respondents selected through the Cross Section/Isedentil sampling technique, namely data collected only at a certain time. The method used is a quantitative approach with moderation regression analysis using the help of smart PLS software. The results of the study indicate that student development does not have a significant effect on academic outcomes and learning satisfaction. In addition, the implementation of AI has been shown to positively moderate the relationship, which means that the use of AI strengthens the influence of student development on improving academic performance and learning satisfaction. These findings recommend optimizing the use of AI-based technology in the learning process to improve the quality of higher education, especially in the field of economics.